Therapeutic potential of human induced pluripotent stem cell–derived cardiac tissue in an ischemic model with unloaded condition mimicking left ventricular assist device - Heima, Daisuke; Takeda, Masafumi; Tabata, Yasuhiko; Minatoya, Kenji; Yamashita, Jun K.; Masumoto, Hidetoshi (The Journal of thoracic and cardiovascular surgery, 2024)
This study aimed to explore the therapeutic potential of human induced pluripotent stem cell (hiPSC)-derived cardiac tissues (HiCTs) in the emerging approach of bridge to recovery for severe heart failure with ventricular assist devices. We used a rat model of heterotopic heart transplantation (HTx) to mimic ventricular assist device support and heart unloading. HiCTs were created by inserting gelatin hydrogel microspheres between cell sheets made from hiPSC-derived cardiovascular cells. Male athymic nude rats underwent myocardial infarction (MI) and were divided into the following groups: MI (loaded, untreated control), MI + HTx (unloaded, untreated control), MI + HTx + HiCT (unloaded, treated), and MI + HiCT (loaded, treated). HiCTs were placed on the epicardium of the heart in treated groups. We evaluated HiCT engraftment, fibrosis, and neovascularization using histologic analysis. After 4 weeks, HiCTs successfully engrafted in 5 of 6 rats in the MI + HTx + HiCT group (83.3%). The engrafted HiCT area was greater under unloaded conditions (MI + HTx + HiCT) than loaded conditions (MI + HiCT) (P < .05). MI + HTx + HiCT had a significantly smaller infarct area compared with MI and MI + HTx. The MI + HTx + MiCT group exhibited greater vascular density in the border zone than MI and MI + HTx. HiCT treatment suppressed cardiomyocyte atrophy due to left ventricular unloading (P = .001). The protein level of muscle-specific RING finger 1, an atrophy-related ubiquitin ligase, was lower in the MI + HTx + HiCT group than in MI + HTx (P = .036). Transplanting HiCTs into ischemic hearts under unloaded conditions promoted engraftment, neovascularization, attenuated infarct remodeling, and suppressed myocyte atrophy. These results suggest that HiCT treatment could contribute to future advancements in bridge to recovery.